Human saliva as a source of biochemical genetic markers. II. genetic interpretations and possible utilization - Teng, Yao Sheng; Tan, Soon Guan (Karger, 1979)
Human saliva enzymes are compared to analogous blood enzymes. The genetic interpretations for variants of several saliva proteins are reviewed. The possible use of human saliva enzymes and proteins in population genetic studies and disease diagnosis is discussed.